KANT'TA TRANSANDANTAL BEN BÎLÎNCİ - Sahabettin Yalçın (Felsefe Dünyası)
This paper examines one of Kant's most controversial concepts, namely the 'transcendental apperception'. Kant introduces this notion primarily for epistemological reasons, as it plays a crucial role in the formation of knowledge. Although the transcendental apperception does not provide any substantial a priori knowledge about the nature of the thinking self - because we do not have any intuition of this self; Kant rejects the existence of intellectual or a priori intuition in human beings - it nevertheless yields pure a priori awareness of its existence and functions. This pure self-consciousness is neither an intuition nor even a concept, but rather an empty 'thought'. The thinking self which is characterized by Kant as the formal or the logical subject of thought, functions as the source of the categories and a priori principles of experience. As I have tried to show in this paper, however, Kant's notion of the transcendental apperception faces some serious problems which affect his theory of knowledge in general.